2022
DOI: 10.1093/eurheartj/ehac544.2117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frailty on in-hospital outcomes after transcatheter mitral valve repair

Abstract: Background Mitral regurgitation (MR) is a common valvular disorder associated with significant morbidity and mortality. Transcatheter mitral valve repair (TMVr) is a minimally invasive procedure indicated for the treatment of selected patients with moderate-severe or severe primary MR. Despite a lack of a universal definition, frailty has been associated with poor post-procedural outcomes. Albeit several trials have examined individual prognostic factors in this population, there is a paucity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Data regarding frailty in TEER or TMVR are largely based on population cohort studies using frailty scores calculated from hospital administrative data, rather than individual patient assessments. Three large population level cohort studies have used the Johns Hopkins Adjusted Clinical Groups Frailty‐Defining Diagnoses Indicator (ACG) to define frailty 53–55 . Hadaya et al found an independent association between frailty and in‐hospital mortality (adjusted odds ratio [OR]: 1.8, 95% CI: 1.2–2.6; p < 0.001), in‐hospital complications, nonhome discharge, and excessive resource utilization in 18,791 patients undergoing TEER between 2016 and 2018, 11.6% of whom were identified as frail 54 .…”
Section: Current Literature: Frailty and Transcatheter Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data regarding frailty in TEER or TMVR are largely based on population cohort studies using frailty scores calculated from hospital administrative data, rather than individual patient assessments. Three large population level cohort studies have used the Johns Hopkins Adjusted Clinical Groups Frailty‐Defining Diagnoses Indicator (ACG) to define frailty 53–55 . Hadaya et al found an independent association between frailty and in‐hospital mortality (adjusted odds ratio [OR]: 1.8, 95% CI: 1.2–2.6; p < 0.001), in‐hospital complications, nonhome discharge, and excessive resource utilization in 18,791 patients undergoing TEER between 2016 and 2018, 11.6% of whom were identified as frail 54 .…”
Section: Current Literature: Frailty and Transcatheter Interventionsmentioning
confidence: 99%
“…Lopez et al described outcomes from a cohort of 30,660 TEER patients, 9.6% of which was considered frail. Frailty was associated with increased in‐hospital mortality (adjusted OR: 2.1, 95% CI: 1.3–3.5, p < 0.001) and nonhome discharge 55 . Kundi et al used the Hospital Frailty Risk Score (HFRS) to describe outcomes for 3746 patients who underwent TEER in 2016.…”
Section: Current Literature: Frailty and Transcatheter Interventionsmentioning
confidence: 99%
See 1 more Smart Citation